Management of refractory lupus nephritis: challenges and opportunities - Golovach, I.Yu.; Yehudina, Ye.D. (KIDNEYS, 2021)
The development of refractory lupus nephritis (LN) indicates an inadequate response to the therapy, which implies the preservation or worsening of the disease activity, despite the therapy. However, the definition of LN is ambiguous, given the lack of clear response parameters: the study of proteinuria and renal function does not give a clear difference between activity and irreversible damage. Understanding the causes of refractory disease and developing treatment strategies are very important since in such patients the prognosis is extremely unfavourable in the form of the development of the end-stage renal disease. This review explores the current concept of refractory LN and summarizes the treatment approaches used in observational cohort studies and case series. We emphasize the importance of optimizing patient adherence to immunosuppressive and supportive therapeutic strategies, as well as avoiding diagnosis delay. Treatment options include a higher dose of glucocorticoid, switching between cyclophosphamide and mycophenolate mofetil, or adding rituximab, which could potentially be combined with belimumab. Less evidence confirms the effectiveness of extracorporeal treatment (plasma exchange or immunoadsorption), calcineurin inhibitors (cyclosporin A or tacrolimus), intravenous immunoglobulin and stem cell transplantation in the treatment of LN. Improvements in understanding what refractory LN is can be integrated into treatment pathways and improve outcomes of LN